The Influence of Tax Awareness, Tax Sanctions, and Risk Preference on Taxpayer Compliance - Irwansyah, Irwansyah (Yayasan Gema Bina Nusantara, 2026)
This study examines the influence of tax awareness, tax sanctions, and risk preference on motor vehicle taxpayer compliance in Bengkulu Province, Indonesia. Although previous studies have identified these variables as important determinants of tax compliance, their findings remain inconsistent, particularly in regional contexts where taxpayer behavior is shaped by local enforcement, tax literacy, and social conditions. This study addresses that gap by integrating the three variables within the Theory of Planned Behavior framework and testing them in the Bengkulu context. A quantitative survey was conducted using purposive sampling with 100 motor vehicle taxpayers registered at SAMSAT offices in Bengkulu Province. Data were analyzed using multiple linear regression. The results show that tax awareness, tax sanctions, and risk preference all have positive and significant effects on taxpayer compliance. The findings suggest that improving taxpayer compliance requires not only stronger enforcement, but also increased awareness and behavioral interventions that reduce non-compliance tendencies. This study contributes by providing context-specific evidence from Bengkulu Province and by extending the understanding of tax compliance through a behavioral perspective.